2018
DOI: 10.1186/s12951-018-0337-2
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-DNA nanoparticles enhanced the immunogenicity of multivalent DNA vaccination on mice against Trueperella pyogenes infection

Abstract: BackgroundTrueperella pyogenes is a commensal and opportunistic pathogen that normally causes mastitis, liver abscesses and pneumonia of economically important livestock. To develop efficacious and potent vaccine against T. pyogenes, chimeric gene DNA vaccines were constructed and encapsulated in chitosan nanoparticles (pPCFN-CpG-CS-NPs).ResultsThe pPCFN-CpG-CS-NPs consists of the plo, cbpA, fimA, and nanH gene of T. pyogenes and CpG ODN1826. It was produced with good morphology, high stability, a mean diamete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 48 publications
2
47
0
1
Order By: Relevance
“…To prevent bronchitis caused by respiratory syncytial virus (RSV), chitosan-DNA nanospheres administered intranasally induced the expression of corresponding protein, and improved the levels of anti-RSVspecific IgG, sIgA, cytotoxic T lymphocytes, and IFN- [62]. The chitosan-DNA nanoparticles were effective against diseases of the T. pyogenes infection and provided strategies for further development of novel vaccines encapsulated in chitosan nanoparticles [63].…”
Section: Chitosan-based Nanoparticlesmentioning
confidence: 99%
“…To prevent bronchitis caused by respiratory syncytial virus (RSV), chitosan-DNA nanospheres administered intranasally induced the expression of corresponding protein, and improved the levels of anti-RSVspecific IgG, sIgA, cytotoxic T lymphocytes, and IFN- [62]. The chitosan-DNA nanoparticles were effective against diseases of the T. pyogenes infection and provided strategies for further development of novel vaccines encapsulated in chitosan nanoparticles [63].…”
Section: Chitosan-based Nanoparticlesmentioning
confidence: 99%
“…Helicobacter pylori, a causative agent of gastritis, duodenal ulcers, gastric ulcer and cancer [29], is an opportunistic and infectious bacterium not only in humans, but also in animals. The infection rates are over 50.8% in developing countries whereas they are more than 34.7% in developed countries [30].…”
Section: Discussionmentioning
confidence: 99%
“…Intramuscular immunization is very effective in eliciting humoral and cellular immune responses. Previous researches have proved that virulence genes enhance the immunity of the vaccine, and chitosan provides longer residence times by intramuscular infection [29,42], allowing the vaccine to access the lymphoid tissue better and resulting in increased IgG production. Therefore, our study further confirmed the stimulation effect of humoral immune responses of cagW and chitosan in mice in comparison to the background signal stimulated by pcDNA3.1 (+) and PBS.…”
Section: Discussionmentioning
confidence: 99%
“…Intramuscular immunization is very effective in eliciting humoral and cellular immune responses. Previous researches have proved that virulence genes enhance the immunity of the vaccine, and chitosan provides longer residence times by intramuscular infection [29,42], allowing the vaccine to access the lymphoid tissue better and resulting in increased IgG production. Therefore, our study further…”
Section: Discussionmentioning
confidence: 99%